PENGARUH PEMBERIAN CAMPURAN DEDAK DAN AMPAS TAHU FERMENTASI DENGAN Monascus purpureus TERHADAP PERFORMA BURUNG PUYUH - Muslim Muslim; Nuraini Nuraini; Mirzah Mirzah (State Islamic University of Sultan Syarif Kasim Riau, 2012)
This study aims to know how and limits the influence of the bran and dried tofu by-product fermentation (DATF)with monascus purpureus against quails performance. This research using quail japan (Coturnix coturnix japonica) phaselayer was five weeks 200 tail. Research methods used are experimental methods to a draft betatesting random draft complete(RAL) using 4 treatment by DATF different level in rations namely A (0% DATF), B (4% DATF,) C (8% DATF) and D(12 % DATF) by deut five times. Rations arranged iso protein 20% and iso calories 2800 Kcal per kg. Parameters observedare performance (consumption rations (gram/tails/day), the production of eggs (daily quail day productions %), heavy eggs(grams/grains ) the egg mass (gram/tails/day) conversion rations, income overs feeds cost) quails. The result analysis showsdiversity use DATF to 12% in rations level markedly dissimilar exert (P<0,05) against rations, consumption daily, theproduction of eggs and differs very real (P<,01) against heavy eggs the mass of eggs, conversion rations quails. According tothis research result can be concluded that level DATF use products to 12% in rations quails can improve its performancequails. On this condition obtained consumption rations 22,16 grams/tails/day, tails the production of eggs (daily quail day,78% productions) heavy 9,67 grams/grains, eggs the egg mass 4,98 grams/tails/day, tail conversion rations 4,44, incomeovers feeds cost Rp. 108,34